Analysis of Factors Affecting the Results Student Learning in Accounting Students Accounting Expertise Program - M. Yusuf A. Ngampo (Universitas Negeri Makassar, 2021)
The research is aimed to determine the factors of interest in learning, and learning disciplines that affect student learning outcomes accounting expertise. This type of research is qualitative research using qualitative descriptive analysis tools and multiple regression analysis to determine how much these factors influence. The sample is 76 students using proportional random sampling technique. This study means that the interest variable (X1) has a positive effect on learning outcomes (Y). This indicates that if the interest variable increases one unit, while the student learning discipline variable is considered constant it will cause an increase in learning outcomes by 0.480. This indicates that when the learning discipline variable has increased by one unit and the interest variable is considered constant it will cause an increase in learning outcomes. learning outcomes of 0.477. The results of the correlation coefficient analysis obtained a value (r) of 0.640, which means that the relationship between student learning outcomes and student learning interest and student learning discipline is in the strong category. Where the correlation value is in the coefficient interval 0.60 - 0.799. While the coefficient of determination (r2) is 0.410 or 41 percent, which means that the effect of student interest in learning and learning discipline on student learning outcomes is 41 percent, while the remaining 59 percent (100% - r2) is determined by other factors not included in this study. The results of the t-test show that the significant value is smaller than the alpha value, where the significant value = 0.002 <alpha = 0.05, which means that it is significant, so the hypothesis proposed is that: